SOCIAL MEDIA AS SYMBOLIC SPACE: IMPLICATIONS OF SYMBOLIC INTERACTIONISM ON GENERATION Z SELF-IMAGE AND SELF-ACCEPTANCE - Tengku Siti Nurhaliza; Nabella Dananier (Universitas Negeri Medan, 2025)
This qualitative study investigates how female Generation Z undergraduates construct self-image and negotiate self-acceptance via Instagram interactions using the theoretical framework of symbolic interactionism. Data were collected through in-depth interviews, digital observations, and documentation involving five purposively selected participants from Tazkia University. Findings reveal that participants strategically manage self-image by curating visual content, ensuring feed aesthetics, and applying filters/editing. A clear separation of digital identities emerged, with a public-facing first account and a more personal second account. Digital cues, such as likes, comments, and shared content posts, act as social validation, influencing self-perception and emotional well-being. Self-acceptance involves reflecting on digital experiences, embracing personal attributes, and seeking offline support. Participants also adapt to social media pressures and algorithms by restricting audiences, using 'close friends' features, and deactivating accounts for self-stability. This study confirms Instagram as a symbolic space where individuals actively shape and negotiate identity and self-worth within a dynamic social context.